EFFECT OF A LAYER-BY-LAYER ASSEMBLED ULTRA-THIN FILM ON THE SOLID ELECTROLYTE AND LI INTERFACE - Tolganbek, Nurbol; Sarsembina, Madina; Nurpeissova, Arailym; Kanamura, Kiyoshi; Bakenov, Zhumabay; Mentbayeva, Almagul (Nanoscale Advances, 2022)
Advanced all-solid-state batteries are considered as the most preferable power source for the next generation devices. Such batteries demand consumption of electrode materials with high energy and power density. One of the excellent solutions is the utilization of Li metal as anode which provides opportunity to fulfill such requirements. Yet, obstacles such as interfacial impedance and reactivity of Li metal with promising solid electrolytes prevent the consumption of the Li anode. Despite its outstanding stability under ambient conditions, high ionic conductivity and facile synthesis methods, NASICON-type Li1.3Al0.3Ti1.7(PO4)3 also suffers from the above mentioned problems. In this work, these critical issues were resolved by applying an artificial protective interlayer. Herein, the layer-by-layer polymer assembly approach of the ultra-thin interlayer of (PAA/PEO)30 on either side of solid electrolyte pellets simultaneously is presented. The introduction of the protective layer prevented a formation of mixed conduction interphase and effectively decreased the interfacial impedance. A symmetric cell with Li metal electrodes performed over 600 hours at 0.1 mA cm−2. Furthermore, an all-solid-state Li metal battery, assembled with the modified LATP solid electrolyte and LiFePO4 cathode, demonstrated an excellent electrochemical performance with an initial discharge capacity of 115 mA h g−1 and a capacity retention of 93% over 20 cycles with a coloumbic efficiency of almost 100%. The LATP with the (PAA/PEO)30 coating exhibited electrochemical stability up to 5 V.
Keywords: Type of access: Open Access; all-solid-state batteries; Li metal